SURG-15. PITUITARY SPINDLE CELL ONCOCYTOMA: A CASE REPORT AND LITERATURE REVIEW. (12th November 2021) - Taka, Taha; Yang, Chen Yi; Limbo, Joshua; Chan, Alvin; Davies, Jordan; Kuan, Edward; Turner, Scott; Hsu, Frank P K
Abstract: BACKGROUND: Spindle cell oncocytoma (SCO) of the pituitary gland is an extremely rare non-functional WHO grade 1 tumor. SCO are often misdiagnosed as nonfunctional pituitary adenomas on pre-operative imaging. They are often hypervascular and locally adherent, which increases hemorrhage risk and limits surgical resection, leading to increased risk of recurrence. We report a case of SCO treated at our institution and provide a review of the current literature. METHODS: A 75-year-old male with a history of hypertension, left thalamic stroke, Parkinson's disease, and normal pressure hypertension presented to neurosurgery clinic with bitemporal hemianopsia, hyponatremia, and abnormal gait and mobility. Imaging showed an enhancing intra- and suprasellar, hyperdense tumor mass measuring 3.0 cm in diameter. We performed a systemic literature search in the PubMed database to identify previous reports of spindle cell oncocytoma. After exclusion of studies that did not meet criteria, 32 publications were selected for critical reading. RESULTS: The patient underwent an endoscopic transsphenoidal resection of the tumor via a multi-disciplinary team. The tumor was fibrous and adherent to the intrasellar dura, with gross invasion of the diaphragm sella, necessitating partial resection of the diaphragm. The defect was repaired, and the patient made an uncomplicated recovery. Post-operatively, the patient experienced improved vision. Upon literature review, SCO present in older adults with an average age of 56.2 ± 14.7 with visual deficits (67.9%), headache (33.3%), hypopituitarism (24.7%), and nausea (11.1%). Full resection was achieved in 38.6% of cases leading to recurrence rate of 23.5% with an average time until recurrence of 32.5 months (range 1-120 months). CONCLUSION: Careful surgical technique is needed due to SCO hypervascularity and strong adherence to minimize risk of injury to surrounding neurovascular structures. Long-term follow up is recommended due risk of recurrence.